Design and Development of an Automated Multi Axis Solar Tracker Using PLC - Santhosh Krishna Venkata; J S Rajshekar (Bulletin of Electrical Engineering and Informatics, 2013)
Design of a two dimensional automated solar tracking system is discussed in this paper. The objectives of the proposed work are to design an automated tracking technique using Light Dependent Resistance (LDR), and solar panel power output to position the solar panel to absorb maximum energy. For positioning the solar panel two stepper motors are used, each for positioning in a plane. These stepper motors were driven by a Programmable Logic Controller (PLC).  The controller is designed using wonderware software considering the inputs from LDR Sensor and solar panel output to drive the stepper motor connected to solar panels. Then the whole program is implemented with the help of PLC. The system was tested on a real time and results showed the proposed technique had improved the efficiency of solar panel by an amount of 25%.